Mesa Redonda, denominada, ¿Qué debes de saber antes de ir a tus prácticas? - Llivi Ruilova, Danny Vicente (2024)
As part of the activities organized for the 35 years of academic creation of the Nursing career, of the Faculty of Health and Human Sciences of the UEB; The Round Table was held, called, What should you know before going to your internship?, which was attended by Dr. Silvana López Paredes, Dean; Teaching staff and students. During its development, seventh cycle students told their experiences during their pre-professional practices in the community and in the hospital setting.